Exploring cherry tomato quality in response to varied watering regimens and growing structures - Kusumiyati Kusumiyati; Farhan Ahmad; Muhamad Aditia Ghifari; Mochamad Arief Soleh; Muhammad Rabnawaz Khan; Rahmat Budiarto; Syariful Mubarok; Yusuf Eka Maulana (Agrosystems, Geosciences & Environment)
Abstract Cherry tomatoes (Solanum lycopersicum) are a high‐value vegetable worldwide. Tomato quality, which can influence nutritional value, is an essential factor for consumer choice. A research study conducted between December 2022 and May 2023 aimed to optimize the quality of cherry tomato cultivars Ruby and Fortesa. The study examined the effects of various watering capacities and growth structures. The study used a randomized complete design with a post hoc Tukey test and found that the cultivar selection was crucial, with Fortesa outperforming other cultivars regarding yield and quality parameters. Ruby simultaneously performed exceptionally well in characteristics such as fruit glucose content and antioxidant activity. Furthermore, the kind of growing structure had significant consequences; greenhouse and rain shelter designs produced higher output and higher quality tomatoes. Watering capacity continuously increased water‐use efficiency, especially at 50% of the evapotranspiration coefficient (ETc). These results highlight the critical role that cultivar selection, growing structures, and watering capacities play in optimizing cherry tomato yield and quality, and they may have future ramifications for sustainable agriculture and nutrition‐focused projects.